Research Trends in Disruptive Technologies for Accounting of The Future – A Bibliometric Analysis - Atanasko Atanasovski; Todor Tocev (Journal of Accounting and Management Information Systems (JAMIS), 2022)
Research Question - Is there a gap in research preferences on disruptive technologies between academia and practitioners? Motivation - Disruptive technologies in accounting represent a new evolutionary phase of accounting impacted by emerging technologies that are part of industrial revolution 4.0. The relevance of emerging technologies, their potential, and the opportunities they offer for the accounting profession attract both academia and professionals with accelerated research efforts. Academia and scientific researchers must research and provide an appropriate theoretical basis to help practitioners better adapt and increase their awareness and trust in technology. Idea - This paper provides early quantitative research data on publication trends related to most disruptive technologies in accounting such as big data, data analytics, cloud, artificial intelligence, and blockchain. Data - The data were collected through detailed analysis and research of websites and publishing platforms on Big Four accounting firms, professional accounting associations, and institutes, and selected high-ranking journals for the period from 2016 to 2020. Tools - The research was conducted using bibliometric analysis to identify how many articles were published by individual parties. Findings - The results highlight that there are no significant discrepancies or different views of academia and practitioners. It is a positive result indicating that academia and scientific researchers exploit in the same direction as practitioners, thus providing support for adaptation and alignment to technology trends. Contribution - The significance of the results of such research is important for obtaining directions in which the academy should research in the future but also for the regulators as well.
Keywords: M15; M41; O33; 650; big data; blockchain; accounting; emerging technologies; cloud; data analytics